Juan Luis Vives - Havu, Kaarlo, author.
1 online resource.
Keywords: "By looking at rhetoric and politics, this book offers a novel account of Juan Luis Vives' intellectual oeuvre. It argues that Vives adjusted rhetorical theory to a monarchical context in which direct speech was not a possibility, demonstrated how Erasmian languages of ethical self-government and political peace were actualized rhetorically and critically in a princely environment and, finally, rethought the cognitive and emotional foundations of humanist rhetoric in his late and famous De anima et vita (1538). Ultimately, towards the end of his life, Vives epitomized a distinctively cognitive view of politics; he maintained that political concord was not a direct outcome of institutional or legal reform or of the spiritual transformation of the Christian world (an optimistic Erasmian interpretation), but that concord could only be upheld once the dynamics of emotions that motivated political action were understood and controlled through responsible rhetoric that respected decorum and civility"--